3D-bioprinted cancer-on-a-chip: level-up organotypic in vitro models. Issue 4 (April 2022) - Monteiro, Maria V.; Zhang, Yu Shrike; Gaspar, Vítor M.; Mano, João F.
Abstract : Combinatorial conjugation of organ-on-a-chip platforms with additive manufacturing technologies is rapidly emerging as a disruptive approach for upgrading cancer-on-a-chip systems towards anatomic-sized dynamic in vitro models. This valuable technological synergy has potential for giving rise to truly physiomimetic 3D models that better emulate tumor microenvironment elements, bioarchitecture, and response to multidimensional flow dynamics. Herein, we showcase the most recent advances in bioengineering 3D-bioprinted cancer-on-a-chip platforms and provide a comprehensive discussion on design guidelines and possibilities for high-throughput analysis. Such hybrid platforms represent a new generation of highly sophisticated 3D tumor models with improved biomimicry and predictability of therapeutics performance. Highlights: The development of 3D in vitro models recapitulating key tumor microenvironment hallmarks is in high demand due to their potential for fostering new discoveries in cancer pathophysiology and for improving preclinical drug screening. Tumor models combining biofabrication and organ-on-a-chip technologies open unique avenues in bioengineered tumor surrogates, which enclose key elements that are generally overlooked in standard 3D platforms. Biofabricated 3D in vitro models on perfusable chips have provided significant advances, yet, addressing untapped microenvironment-specific designs and bioengineering parameters will be key for further improving biomimicry. Next-generation patient-derived 3D-bioprinted cancer-on-a-chip platforms are expected to level-up current approaches, ultimately enabling the generation of increasingly physiomimetic tumor models for precision/personalized medicine.